Diversidade e composição da ictiofauna de igarapés da Calha Norte paraense - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The Calha Norte of the state of Pará is located on the left bank of the lower Amazon River, comprising nine municipalities in the mesoregion of the lower Amazon. The work seeks to provide data on the richness, abundance and diversity of the fish fauna of two drainage systems (Maicuru and Curuá rivers), in two Amazonian seasonal periods (dry and flood), making a survey of the occurrence of the fish fauna of streams of the region. The collections were carried out in 12 sampling points, 6 points in the Maicuru river drainage and 6 in the Curuá river drainage. Sampling took place from December 1 to 6, 2020 and July 6 to 10, 2021, referring to the dry and flood periods, respectively. Fish were collected with trawls and sieves in 1st to 3rd order streams. The ichthyofauna of streams in Calha Norte Paraense was inventoried and a list of species is presented. Among the most abundant species for the dry season, the following stand out: Hemigrammus bellottii (N=679), M. melogramma (N=253) and H. copelandi (N=248), in the wet season the species H. bellottii stand out (N=1987), H. ocellifer (N=745) and Serrapinnus sp. (N=459). Highlighting 51 exclusive species (in the collections of the two periods) for the Curuá river, and 28 for the Maicuru river. In addition to the quantitative, thirty-one species were recorded with great potential to be new to science. The Two-way PERMANOVA analysis detected statistical significance both in the composition and in the sampled periods and drains. Ascertaining that there is a dissimilarity in the composition of the ichthyofauna between the dry and flood periods and between the drainages of the Curuá and Maicuru rivers. We provide data from a survey of the ichthyofauna of igarapés in the Calha Norte region, which still has few works registered in the area. Presenting relevant information to support future studies and decision-making in the management of the region's ichthyofauna, since it is an area with great influence of livestock.
Keywords: Amazônia; Drenagens; Ecologia; Peixes; Pará; CNPQ:: CIÊNCIAS BIOLÓGICAS